MDMB-CHMICA: Availability, Patterns of Use, and Toxicity Associated With This Novel Psychoactive Substance. (28th January 2017) - Haden, Mark; Archer, John R. H.; Dargan, Paul I.; Wood, David M.
ABSTRACT: Background : MDMB-CHMICA (methyl 2-[[1-(cyclohexylmethyl)indole-3-carbonyl]amino]-3, 3-dimethylbutanoate) is a synthetic cannabinoid receptor agonist that has been detected in several recreational drug products in Europe since August 2014. Objectives: This article aims to describe the prevalence of use, availability, and desired and adverse effects of MDMB-CHMICA. Methods : Data were collated from published scientific literature, and systematic searches were conducted of publically available Internet sources (the "gray literature"), including websites offering to sell MDMB-CHMICA and Internet discussion forums featuring user reports. Results : There are two case reports of fatalities in the published literature and one series of analytically confirmed cases of intoxication with MDMB-CHMICA. Seventy-eight websites offered to sell MDMB-CHMICA and a range of quantities were available with discounts for purchase of larger quantities (from 0.25 g at $27.95/g to 100 kg at $1.28/g). We identified 36 reports from MDMB-CHMICA users on Internet discussion forums dated October 2014 onwards. The most common positive effect reported by users was euphoria (11; 30.6%) and almost all reports (33; 91.7%) described one or more adverse effects, most commonly palpitations (11; 30.6%), vomiting (9; 25.0%), loss of consciousness (6; 16.7%), visual hallucinations (6; 16.7%), chest pain (5; 13.9%), and anxiety (5; 13.9%). Conclusions : This systematic review of qualitative and scientific data relating to MDMB-CHMICA shows that it is widely available from Internet-based suppliers. Users describe a spectrum of effects that are consistent with other synthetic cannabinoids, but there was a high prevalence of adverse effects, and both users and suppliers warn of its high potency.